Digital Branding Transformation of Construction Services through the TikTok Platform : A Preliminary Analysis of Potential and Challenges at Havana Sulung Mandiri - Dimas Setiawan; Ridho Pamungkas; M. Naf’an; Galang Romadhona (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study examines the potential for digital branding transformation of Mitra Havana Sulung Mandiri, a construction service company in East Java, through the utilization of TikTok as a promotional platform. Using observations and interviews, the research identified strong visual content opportunities from the company’s activities, such as documenting construction progress, showcasing before-and-after project visuals, and sharing client testimonials. These elements offer significant storytelling potential for engaging online audiences. However, several internal barriers hinder optimal implementation. These include limited digital literacy among staff, inadequate content creation tools, and the absence of standardized procedures for producing and publishing content. Externally, skepticism toward social media marketing in the construction sector and the unpredictability of TikTok’s algorithm also create challenges. Thematic analysis revealed three primary needs: maximizing existing visual assets to create compelling narratives, enhancing internal capacity through targeted digital training, and developing a culture that supports continuous digital engagement. To address these, the study proposes an initial strategy involving educational content, behind-the-scenes videos, and a clear content production guide. In addition, it suggests forming a dedicated social media team, running a 30-day continuous content campaign, and collaborating with local creators to expand reach. These recommendations align with existing literature on the role of short-form video in increasing brand awareness, credibility, and trust in service-oriented industries. By integrating strategic content planning, capacity building, and consistent online engagement, construction SMEs can position themselves competitively in the evolving digital marketplace. The case of Mitra Havana Sulung Mandiri demonstrates that even in traditionally offline industries, leveraging TikTok can offer a pathway toward brand differentiation and long-term audience growth.